TLR4 Cross-Talk With NLRP3 Inflammasome and Complement Signaling Pathways in Alzheimer's Disease - Yang, Junling; Wise, Leslie; Fukuchi, Ken-ichiro (Frontiers in Immunology, 2020)
Amyloid plaques, mainly composed of abnormally aggregated amyloid β-protein (Aβ) in the brain parenchyma, and neurofibrillary tangles (NFTs), composed of abnormal aggregates of hyperphosphorylated tau protein in neurons, are two pathological hallmarks of Alzheimer’s disease (AD). Fibrillar Aβ deposits and tau aggregates in the brain are accompanied with neuroinflammation and synapse loss, characterized by activated microglia and dystrophic neurites. Genome-wide association studies on patients with late-onset AD have identified a dozen genetic risk variants that are involved in innate immune responses, highlighting the importance of immune cells in the pathogenesis of late-onset AD. Additional lines of evidence support the notion that activated microglia, innate immune cells in the central nervous system (CNS), play pivotal, dual roles in AD progression: either clearing Aβ deposits by phagocytosis and promoting neuron survival and plasticity or releasing cytotoxic chemicals, inflammatory cytokines, exacerbating Aβ load and synaptotoxicity. Aggregated Aβ binds to toll-like receptor 4 (TLR4) and activates microglia, resulting in increased phagocytosis and cytokine production. Complement components are associated with amyloid plaques and NFTs. Aggregated Aβ can activate complement, leading to synapse pruning and loss by microglial phagocytosis. Systemic inflammation can activate microglial TLR4, NLRP3 inflammasome, and complement in the brain, leading to neuroinflammation, Aβ accumulation, synapse loss and neurodegeneration. The host immune response has been shown to function through complex crosstalk between the TLR, complement and inflammasome signaling pathways. Accordingly, targeting the molecular mechanisms underlying the TLR-complement-NLRP3 inflammasome signaling pathways can be a preventive and therapeutic approach for AD.